G227(P) Starting out on a clinical academic pathway: the experience of a newly – qualified nurse. (27th April 2015) - Lea, S; Taylor, R; Gibson, F
Abstract : Aim: The development of clinical academic careers should continue to focus on both clinical and academic work, rather than pursuing one at the expense of the other. What remains a challenge is the articulation of new roles owing to the lack of clarity and shared appreciation of what they are and what they do. As these are relatively new roles, a shared understanding of the activities that clinical academic post holders might undertake have yet to be really clarified. The aim of this work is to reflect upon the experiential learning of a newly – qualified nurse and novice researcher. The focus is on the positive impact of research training on clinical development and vice versa. Methods: A review of the current literature on the topic added to my personal reflection on the benefits and challenges of undertaking a clinical academic career. Results: The literature suggests a lack of clearly defined clinical academic career pathways for nurses during the early stages of their career, which is a key recommendation of the Association of UK University Hospitals (2012). As a result of this, there is a paucity of newly – qualified and junior nurses embarking on a clinical academic pathway. Reflecting on my own experience soon after qualifying of combining a research role within a large research team with clinical practice, there are great benefits to developing both roles early in a career, although there can also be some challenges, one example being the time pressures of juggling two roles. Conclusion: From my experience, I will discuss suggestions to help novice nurses participate in research activity and how to address some of the challenges I have faced, sharing real examples of the benefits. This pathway has been highly dependent on the collaboration between health services and higher education institutions, with support provided from both. I will discuss my support needs as a less experienced nurse juggling two multi-faceted roles. The literature and my personal experience indicate that there would be great benefits to patients, the nursing workforce, and academic and health institutions if more nurses step on to a clinical academic pathway earlier in their career trajectories.